Explaining immigration preferences: Disentangling skill and prevalence. (October 2017) - Malhotra, Neil; Newman, Benjamin
One of the most important and consistent findings to emerge from the study of immigration politics over the past decade is the seemingly uniform preference among mass citizenries for high-skilled immigrants. One potential conceptual flaw in this mounting body of literature is that skill is confounded with prevalence: people may prefer high-skilled immigrants not because they are skilled but because there are not very many of them. To address this possibility, we conducted an original experiment within a nationally representative survey of over 12, 000 respondents. We conducted three main empirical tests and found that the skill premium is not confounded by prevalence. However, low-skilled Mexican immigrants specifically are disadvantaged when people are told that they are prevalent, a finding that comports with extant research on the construction of Latino immigration as a unique threat to American society.